Acceptability and Utilization of Livelihood Programs In Higher Education - Hazel Aquino (Camarines Sur Polytechnic Colleges, 2023)
This study evaluated the acceptability and utilization of livelihood programs in Higher Education. The study's respondents were divided into two; for the quantitative data, the respondents were the 75 beneficiaries from the two partner communities of Camarines Sur Polytechnic Colleges (CSPC), while for the qualitative part, there were ten extensionists of CSPC. A semi-structured questionnaire was used to collect the data for the study. Frequency count, mean, and percentage weighted mean were used in the study. Likewise, the following statistical tools were used for the appropriate treatment of gathered data, in observance of the concurrent mixed method design, and to test the relationship, Pearson R was utilized to know the relationship between the two variables of acceptability and utilization of livelihood programs and to test the difference, Anova (two-way) was used. Results of the study showed that the level of acceptability of livelihood programs along the three skills training was interpreted as highly acceptable. Findings further revealed that the extent of utilization of extension programs for all five deliverable are interpreted as highly utilized. Results further showed that the rating of beneficiaries, along with training, community outreach, and technical assistance, have a significant relationship with the level of acceptability and utilization of livelihood programs. In contrast, communication information and technology transfer and utilization have no significant relationship. Likewise, results showed no significant differences in the ratings of beneficiaries on the level of acceptability and utilization along the five deliverable. The extensionists encountered different challenges in implementing the various extension programs. Thus, an action plan was proposed as an intervention strategy based on the study results.